The effect of heat treatment temperature on phase formation and luminescence properties of calcium magnesium silicate glass-ceramics doped with Sm 2 O 3 - Wipada Senanon (2019)
© 2019, © 2019 Taylor & Francis Group, LLC. The transparent glasses of CaO-MgO-Al 2 O 3 -SiO 2 -ZnO system doped with Sm 2 O 3 was prepared by conventional melt-quenching method. The obtained glasses were heat treated at a suitable temperature (875 °C–920 °C for 2 h) identified by differential thermal analysis (DTA). Phase formation and microstructure of glass-ceramics were characterized by X-ray diffraction and scanning electron microscopy, respectively. The optical transmission spectra were recorded by UV-Vis spectrophotometer in the wavelength range between 350 and 1000 nm. It was found that the increase in heat treatment temperature reduced the transparency of the glass-ceramics. The luminescence properties were identified by fluorescence spectroscopy. The excitation spectra of Sm 2 O 3 doped CaO-MgO-Al 2 O 3 -SiO 2 -ZnO glass-ceramic samples are in wavelength range of 550–750 nm and the emission spectra exhibited a strong orange-red luminescence composed of 562, 599 and 654 nm under excited at 402 nm. The results of XRD studies revealed the occurrence of diopside (CaMgSi 2 O 6 ) and akermanite (Ca 2 MgSi 2 O 7 ) phases. The increasing of heat treatment temperature has no effect on the shift of emission spectra.